Practice of quality management in an MSQH accredited hospital: a case study on Bentong Hospital - Abd. Manaf, Noor Hazilah (IIUM Press, 2009)
The objective of the study was to assess the quality management among employees of Bentong Hospital, with particular reference to the frontline health workers comprising medical officers, the nursing staff, medical assistants, pharmacist, and assistant pharmacists, laboratory technologists and health attendants. Instrument developed Manaf (2003) with established psychometric properties was employed for this study. The instrument measures eight factors of quality management namely leadership and management commitment, supplier partnership, continuous improvement, and employee involvement and training, management by fact, strategic planning, teamwork, and quality assurance. Practices was found to be highest for continuous improvement, followed by strategic planning, quality assurance and teamwork respectively. Overall practice of quality management also has a high mean score of 3.90. They also have positive perception on the outcome of quality management implementation.